Recommendations for Increasing the Efficiency of Promotion of Websites in Belarusian Region - E. M. Yelovaya (Цифровая трансформация)
The purpose of the scientific study was to develop practical tools to improve the efficiency of promoting websites of the regions of the Republic of Belarus using the methodology of comparative analysis with the socalled “reference” websites of the districts, i.e. with those districts whose websites are well indexed in search engines, and are also well accessible to all interested parties. The Postavy district was taken as the study area, and the Braslav district was taken as the “reference district”. As a result of applying the methodology, an algorithm for SEO optimization of the website of the Postavy district was developed based on a comparative analysis of the online promotion technology of the Braslav district. As a result, a list of recommendations was developed for SEO-optimization of a website representing Postavy district tourism in order to increase indexing and visibility for users on the Internet.